Dwarfs: The Changing Lives of Archetypal ’Curiosities’ — and Echoes of the Past - Adelson, Betty (Disability Studies Quarterly, 2005)
Can a class of individuals that was once considered among the most prominent of freaks be "defreaked"? And if so, what could cause such a makeover to occur? The answers to these questions are playing out among persons with dwarfism in an increasing number of nations. Although the social roles of many members of this former "freak" population have undergone a transformation during the last half-century, the forces that caused them to be mocked and exploited as they struggled to cope are still very much in evidence.